OC-081 VALIDATION OF THE DATA QUALITY OF THE SPANISH INCISIONAL HERNIA SURGERY REGISTRY (EVEREG). PILOT STUDY. (13th October 2022) - Olona, C; Pereira, J A; Comas, J; Protti, G P; Alonso, V; Amador, S; Bombuy, E; Mitru, C; Gimeno, M; López-Cano, M
Abstract: Aim: The Spanish Incisional Hernia Surgery Registry (EVEREG) is promoted by the Abdominal Wall section of the Spanish Association of Surgeons, starting data collection in July 2012 and currently has more than 13, 500 cases. The objective of this study is to validate the data collected through a pilot audit process Material & Methods: A sample of hospitals participating in the EVEREG registry since 2012 is selected. Patients registered in these centers in the period 2012–2019 are included. A stratified random sampling is carried out, with the inclusion of 10% of registered cases per center with a minimum of 20. In the 2020–2021 period, a selection of researchers, different from that of the center to be audited, checks the concordance between the registry data and the data collected in the patient's clinical history, either in person or online. Results: 330 patients have been analyzed, out of a total of 2673 registered, in 9 participating centers. The average accuracy has been 95.7% (99.1–79.35%). With 1.5% incorrect data and 2.28% missing data Conclusions: This is the first validity study of an abdominal wall registry The accuracy greater than 95% obtained allows us to determine an excellent quality in the data collection of the EVEREG registry. We believe that the confirmation of these data in all the centers participating in the registry would guarantee the quality of the studies carried out and their comparison with other international registries